Mapping a fracture network formed by hydraulic fracturing in a shale gas reservoir - Węglińska, Elżbieta; Leśniak, Andrzej; Pasternacki, Andrzej; Wandycz, Paweł (Geology, Geophysics and Environment, 2024)
Microseismic monitoring is an important technique that can be used to identify fractures in rock mass. The aim of this article is to identify, on the basis of the location of microseismic events, structures formed by hydraulic fracturing in the Wysin-2H/2Hbis horizontal well from the Baltic Basin in northern Poland, and to compare the patterns of these structures with the direction of regional stresses. The authors proposed a novel multi-step workflow for finding these structures. To be able to delineate the structures from microseismic events with greater accuracy, a collapsing algorithm was used. Then, based on the Hierarchical Density-Based Spatial Clustering of Applications with Noise (HDBSCAN) clustering algorithm and the elongation coefficient of each cluster, probable fissures were identified and compared against the maximum horizontal stress direction. In addition, based on the 3D seismic data from the Wysin and the calculated geomechanical parameters in the monitoring well, the probability classes of brittleness indices in the LMR (λρ-μρ) parameter domain were determined. A comparative analysis was performed between the two variants of microseismic event location (before and after the collapsing procedure) and the estimated probability of a given class of brittleness index. The comparison of the event location with the 3D seismic data was used to validate the results before and after collapsing due to the high resolution of the seismic method. It is shown that the collapsed events appeared in more rigid regions, where more energy release is expected.